Bactericidal efficacy of low dose gaseous ozone against clinically relevant multidrug-resistant bacteria - Banerjee, Bob; Thompson, Christine; Nizet, Victor; Bjånes, Elisabet (Frontiers in Microbiology, 2024)
IntroductionHealthcare-associated infections (HAIs) pose a significant challenge in acute care hospitals, particularly in intensive care units, due to persistent environmental contamination despite existing disinfection protocols and manual cleaning methods. Current disinfection methods are labor-intensive and often ineffective against multidrug-resistant (MDR) pathogens, highlighting the need for new, automated, hands-free approaches.MethodsThis study evaluates the bactericidal efficacy of low concentrations of gaseous ozone (5 ppm) against clinically relevant and often MDR bacteria under various concentrations, contact times, temperatures, and environmental conditions.ResultsWe observed a 3 log10-fold reduction in Escherichia coli and Salmonella Typhimurium and a 1–2 log10-fold reduction in group A Streptococcus and methicillin-resistant Staphylococcus aureus upon ozone exposure. The bactericidal effect was dose-dependent, with no significant difference between single and repeated exposures. Environmental conditions such as temperature and humidity had minimal impact on low-dose ozone efficacy, with slightly improved bacterial killing at colder temperatures and higher humidity levels. Gaseous ozone also showed significant bactericidal activity against the broad range of Gram-positive and -negative MDR clinical isolates.DiscussionThese findings highlight the potential of low-dose gaseous ozone as a versatile, effective, and hands-free disinfectant for healthcare and other settings. Further research is needed to establish long-term safety and efficacy guidelines for its use in occupied spaces and to explore potential synergy with other contemporary disinfection strategies.